Platelet-derived microparticles provoke chronic lymphocytic leukemia malignancy through metabolic reprogramming - Gharib, Ehsan; Veilleux, Vanessa; Boudreau, Luc H.; Pichaud, Nicolas; Robichaud, Gilles A. (Frontiers in Immunology, 2023)
Background It is well established that inflammation and platelets promote multiple processes of cancer malignancy. Recently, platelets have received attention for their role in carcinogenesis through the production of microvesicles or platelet-derived microparticles (PMPs), which transfer their biological content to cancer cells. We have previously characterized a new subpopulation of these microparticles (termed mito-microparticles), which package functional mitochondria. The potential of mitochondria transfer to cancer cells is particularly impactful as many aspects of mitochondrial biology (i.e., cell growth, apoptosis inhibition, and drug resistance) coincide with cancer hallmarks and disease progression. These metabolic aspects are particularly notable in chronic lymphocytic leukemia (CLL), which is characterized by a relentless accumulation of proliferating, immunologically dysfunctional, mature B-lymphocytes that fail to undergo apoptosis. The present study aimed to investigate the role of PMPs on CLL metabolic plasticity leading to cancer cell phenotypic changes. Methods CLL cell lines were co-incubated with different concentrations of human PMPs, and their impact on cell proliferation, mitochondrial DNA copy number, OCR level, ATP production, and ROS content was evaluated. Essential genes involved in metabolic-reprogramming were identified using the bioinformatics tools, examined between patients with early and advanced CLL stages, and then validated in PMP-recipient CLLs. Finally, the impact of the induced metabolic reprogramming on CLLs’ growth, survival, mobility, and invasiveness was tested against anti-cancer drugs Cytarabine, Venetoclax, and Plumbagin. Results The data demonstrated the potency of PMPs in inducing tumoral growth and invasiveness in CLLs through mitochondrial internalization and OXPHOS stimulation which was in line with metabolic shift reported in CLL patients from early to advanced stages. This metabolic rewiring also improved CLL cells' resistance to Cytarabine, Venetoclax, and Plumbagin chemo drugs. Conclusion Altogether, these findings depict a new platelet-mediated pathway of cancer pathogenesis. We also highlight the impact of PMPs in CLL metabolic reprogramming and disease progression.